Implementation of Timber Legality Verification System for Forest Processed Wood Products Based on Ecological Justice - Mulyani, Sri; Lisdiyono, Edy (International Journal of Criminology and Sociology, 2021)
This study aims to analyze the application of the Timber Legality Verification System (SVLK) for forest processed wood products, namely furniture in Jepara Regency. SVLK is enforced to maintain harmony between environmental ecosystems and business ecosystems, this is in accordance with the concept of environmental justice which harmonizes environmental, economic and social in Jepara Regency. The research method used is normative-empirical (applied law research). The results showed that the importance of implementing SVLK on furniture in the Jepara Regency can increase the selling value in the global market and guarantee its legality. SVLK is regulated in the Regulation of the Minister of Forestry of the Republic of Indonesia Number: P.38/Menhut-II/2009 concerning Standards and Guidelines for Assessment of Performance of Sustainable Production Forest Management and Verification of Timber Legality in License Holders or in Private Forests. The implementation of SVLK in Jepara Regency for processed forest timber has not been optimal, because many IKMs do not yet have SLKs due to high costs and complicated procedures